PERENCANAAN JELAJAH PUSAKA SEBAGAI DAYA TARIK WISATA DI KOTA SINGARAJA - I Kadek Arya Budi Laksana; Ni. G. A. Diah Ambarwati Kardinal (Pranatacara Bhumandala: Jurnal Riset Planologi, 2020)
The area of the Port of Buleleng is an area that has undergone three periods of government namely the Kingdom of Buleleng, the Dutch East Indies Government and the Sunda Ketjil Government. With this history so that the Port of the Buleleng Port can be utilized as an heirloom that aims to maintain and protect the heritage of existing cultural heritage and provide knowledge to the wider community and also to the government that awareness in maintaining and protecting historic relics of an heirloom is very urgent. This study examines two issues that focus on the condition of the potential inheritance in the Buleleng Port Area and how to protect and preserve cultural heritage in the Port of Buleleng. The results of the study were analyzed using heirlooms modeling by using the four A analysis in tourism planning, namely attractions, accessibility, amenities and institutions.